Current treatment options for esophageal diseases. Issue 1 (8th July 2016) - Martínek, Jan; Akiyama, Jun‐ichi; Vacková, Zuzana; Furnari, Manuele; Savarino, Edoardo; Weijs, Teus J.; Valitova, Elen; van der Horst, Sylvia; Ruurda, Jelle P.; Goense, Lucas; Triadafilopoulos, George
Abstract : Exciting new developments—pharmacologic, endoscopic, and surgical—have arisen for the treatment of many esophageal diseases. Refractory gastroesophageal reflux disease presents a therapeutic challenge, and several new options have been proposed to overcome an insufficient effectiveness of proton pump inhibitors. In patients with distal esophageal spasm, drugs and endoscopic treatments are the current mainstays of the therapeutic approach. Treatment with proton pump inhibitors (or antireflux surgery) should be considered in patients with Barrett's esophagus, since a recent meta‐analysis demonstrated a 71% reduction in risk of neoplastic progression. Endoscopic resection combined with radiofrequency ablation is the standard of care in patients with early esophageal adenocarcinoma. Mucosal squamous cancer may also be treated endoscopically, preferably with endoscopic submucosal dissection. Patients with upper esophageal cancer often refrain from surgery. Robot‐assisted, thoracolaparoscopic, minimally invasive esophagectomy may be an appropriate option for these patients, as the robot facilitates a good overview of the upper mediastinum. Induction chemoradiotherapy is currently considered as standard treatment for patients with advanced squamous cell carcinoma, while the role of neoadjuvant therapy for adenocarcinoma remains controversial. A system for defining and recording perioperative complications associated with esophagectomy has been recently developed and may help to find predictors of mortality and morbidity.